2018
DOI: 10.1007/s00066-018-1340-0
|View full text |Cite
|
Sign up to set email alerts
|

The potential predictive value of tumor budding for neoadjuvant chemoradiotherapy response in locally advanced rectal cancer

Abstract: PurposeThis study was conducted to investigate the potential predictive value of tumor budding for neoadjuvant chemoradiotherapy response in locally advanced rectal cancer.Patients and methodsSurgical specimens of 128 ypUICC (Union for International Cancer Control) stage 0–III mid-to-low rectal cancer patients were identified from a prospectively maintained colorectal cancer database and classified into two groups using the 10 high-power field average method: none/mild tumor budding (BD-0) and moderate/severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…Of the most recent studies, Jäger et al [3] can be compared to our own study. As in our study, they evaluated budding not only at the invasive front but also throughout the tumor.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Of the most recent studies, Jäger et al [3] can be compared to our own study. As in our study, they evaluated budding not only at the invasive front but also throughout the tumor.…”
Section: Discussionmentioning
confidence: 95%
“…Budding has been described as a prognostic feature after chemoradiotherapy in rectal cancer patients in several publications with the general limitation of a retrospective study design. In previous studies, budding was reported in 10.1-63.2% of cases due to different methodologies used for evaluation [3,[15][16][17][18][19][20]. Budding has been shown to be a negative prognostic factor for survival in different kinds of study designs and for a broad range of cut-offs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was an independent marker for dramatically worse overall survival in rectal cancer patients. Prognostic markers are important for accurately individualizing therapies for rectal cancer patients, thereby reducing long-term costs and patient suffering [ 48 , 49 ]. Given the strong prognostic significance in this investigation for rectal cancer patients, additional studies on cell-in-cell structures and senescence are clearly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…All patients received neoadjuvant radiochemotherapy treatment including 50.4 Gy overall dose fractured into 28 sessions of 1.8 Gy and chemotherapy including 5-FU for an overall period of 38 days. 10,11 The tumor response was surveilled 8 weeks post-RCT with proctoscopy, CT of the pelvis, endorectal ultrasound and clinical examination. Thereafter, tumor resection was performed in 191 patients.…”
Section: Treatment Protocolmentioning
confidence: 99%